Pathogenesis of Corynebacterium pseudotuberculosis infection and vaccination trial against caseous lymphadenitis in goats - Mohd Nordi, Nur Adza Rina (2016)
Corynebacterium pseudotuberculosis is a Gram-positive bacterium that isresponsible for a disease called caseous lymphadenitis (CLA) in goats and sheep. This disease has worldwide distributions and the bacterium can remain in the environment for months. It is difficult to eradicate and can be easily transmitted to naive animals. Furthermore, transmission and the pathology of the disease are not fully understood. Therefore, this experiment was conducted to determine the best route of infection of the disease, the clinical and pathological changes in goats following experimental infection, the humoral immune response via antibody titers shown by the infected goats, and the efficacy of a commercial vaccine in preventing CLA in goats in Malaysia. Twenty adult healthy goats were selected and divided into 4 groups. All goats of the first 3 groups were infected with 107 cfu/mL of live C. pseudotuberculosis via three different routes; the intradermal, the intranasal and the oral routes. The last group served as the uninfected control group. The goats were observed daily for clinical signs related to CLA for 30 days experimental period. Rectal temperatures and blood samples were taken periodically. The infected goats from all infected groups were depressed, showed lack of appetite, and increased in body temperature in the first week post-inoculation. The intradermal group had swelling with pus at the site of infection. Blood profile of the goats revealed significant decreased in haemoglobin for the intradermal and intranasal groups. Only the intradermal group showed significantly (p<0.05) high total WBC counts, with the increased neutrophils and monocyte concentrations. Generally, goats infected intradermally showed most severe clinical signs and haematology changes. At the end of 30-day experimental period, all goats were sacrificed. C. pseudotuberculosis was re-isolated from most of the intradermally infected goats with 40% of the goats had the bacteria in the liver, 80% in prescapular and 40% in submandibular lymph nodes. Only 20% of goats in the intranasally infected group had the bacteria in the liver. No bacteria were isolated from any organ or lymph nodes from the oral and control goats. Abscessation was the most commonly observed gross lesions, particularly within the lymph nodes of infected goats. Other less common lesions included consolidation of lung lobes, congestion of kidneys and lymph nodes. Histopathological lesions scores revealed significantly (p<0.05) much severe overall lesions among goats exposed intradermally. Following to the initial 30-day experimental trial, a chronic study was eventually conducted. Nine adult goats were similarly infected intradermally with 107 cfu/mL of live C. pseudotuberculosis and were observed for 3 months. Similarly, all infected goats were less active in week 1 post-infection, developed swelling at the injection site with enlargement of submandibular lymph nodes. The haemoglobin, however, remained within normal value and decresed insignificantly (p>0.05) throughout the experimental period. Total white blood cell (WBC) counts were consistently high until day 39 post-infection due to the increased neutrophilic and monocytic counts. The serum IgG increased and exceeded the cut-off value on day 10 post-infection but most significant (p<0.05) increase was observed on day 14 post-infection before it gradually decreased until day 53 post-infection and approaching the cut-off value at the end of the 90-day experimental period. Three goats were sacrificed by slaughtering monthly. C. pseudotuberculosis was successfully isolated from all lymph nodes with abscessation, and from the lungs of a goat that was sacrificed 2 months post-infection. Prescapular node abscessation was observed in 2 goats at 1 month post-inoculation, in all 3 goats at 2 and 3 months.There was also abscessation in the submandibular lymph node of a goat at 3 month post-inoculation.The lungs of infected goats showed thickening of interalveolar septa, mild to moderate congestion of the liver with inflammatory cells found scattered in between hepatocytes and presence of mild fatty degeneration of the hepatocytes. The kidneys showed congestion of blood vessels and presence ofurinary cast in the renal tubules.The affected lymph nodes showed typical abscess in which the diameter of the necrotic centre was significantly (p<0.05) larger with increase of time post-infection.These results show that the disease progressed with time after infection. Currently, there is only one commercial vaccine for CLA in Malaysia. However, the efficacy was uncertain. Twenty-seven goats of different serological status were selected from a farm with endemic CLA. Group A consisted of 10 seropositive goats, group B with 10 sero-negative goats while group C with 7 seronegative goats that served as control-unvaccinated group. All goats of groups A and B were vaccinated using Glanvac 6TM vaccine twice at 1-month apart. One month after the second vaccination, all goats were challenged with 109 cfu/mL of live C. pseudotuberculosis.The goats were observed for clinical signs and were killed a month post-infection. The bacterium was most frequently isolated from lymph nodes of goats of group A but the rate of isolation showed no significant (p>0.05) difference among all groups. Gross lesion was observed in the prescapular lymph nodes of all groups (p>0.05). The goats vaccinated with Glanvac 6TM either with sero-positive or sero-negative still developed signs and lesions of abscessation similar to the unvaccinated goats. Thus, the vaccine was unable to prevent goats from developing CLA.